Fruits as the vehicle of drug resistant pathogenic yeasts. Issue 3 (September 2017) - Lo, Hsiu-Jung; Tsai, Sheng-Hua; Chu, Wen-Li; Chen, Yin-Zhi; Zhou, Zi-Li; Chen, Hong-Fu; Lee, Ching-Fu; Yang, Yun-Liang
Summary: Objective: We investigated the diversity and drug susceptibility of pathogenic yeasts on fruit surfaces. Method: Fruits were purchased from supermarkets and washed with buffer. The pellets were re-suspended in medium after centrifugation. The cell suspensions were plated onto CHROMagar Candida medium. Yeasts were identified by ribosomal DNA sequencing and their drug susceptibilities were determined by broth microdilution assay. Results: Of 184 isolates, comprised of 55 species, from 22 different types of fruits, 29 species, including Candida famata, Candida fermentati, Candida guilliermondii, Candida intermedia, Candida krusei, Candida orthopsilosis, Candida parapsilosis, Candida pelliculosa, Candida tropicalis, and others have been reported to cause diseases in humans. In addition to C . krusei, intrinsically resistant to fluconazole, all Rhodotorula and Rhodosporidium species were resistant to fluconazole. One each of C . tropicalis isolate was belonged to diploid sequence type (DST)149 and DST225, genotypes also detected in isolates from humans. Furthermore, the DST225 isolate was less susceptible to azole drugs. The susceptibilities to azole drugs for clinical and agricultural usage were associated to each other. Conclusion: It is important to be aware of the existence of pathogenic yeasts, especially drug-resistant ones, on the fruit surfaces, a potential route for pathogenic yeasts to be transmitted to humans.